The Effects of Attentional Focus Instruction on the Performance of a Whole-Body Coordination Task in Children With Developmental Coordination Disorder - Psotta, Rudolf; Abdollahipour, Reza; Janura, Miroslav (Research in developmental disabilities, 2020)
BACKGROUND AND AIM: Previous studies have supported the advantages of an external focus of attention (EFA) relative to an internal focus of attention (IFA) in healthly adults. However, effects of attentional focus instructions on skill performance and acquisition in children are equivocal. The aim of this study was to examine the effects of attentional focus instructions on performance of a whole body coordination task in children with and without developmental coordination disorder (DCD). METHODS: Children with DCD (n = 18) and typically developing (TD) children (n = 21) (9-10 years) were asked to perform 3 countermovement vertical jumps in the IFA (Concentrate on the swing of your arms), EFA (Concentrate on getting as close to the ceiling as possible), and control conditions. RESULTS: The results showed that regardless of children's motor development proficiency, the jump height and vertical take-off velocity (VTO) were higher in EFA relative to both IFA and Con conditions. In addition, VTO was significantly higher in the Con relative to IFA condition. CONCLUSION: The results of the current study showed that EFA relative to IFA instructions could enhance the neuromuscular activation of dynamic contractions of the leg muscles in both children with and without DCD. The findings suggest that the beneficial effects of EFA relative to IFA instructions on children's motor performance is identical across children with different levels of motor proficiency.
Keywords: motorické dovednosti; poruchy motorických dovedností; lidé; Case-Control Studies; mužské pohlaví; studie případů a kontrol; biomechanika; dítě; Child; Humans; Attention; Male; pozornost; Biomechanical Phenomena; Motor Skills Disorders; Motor Skills; ženské pohlaví; Female